Influencing factors and adverse outcomes of virologic rebound states in anti-retroviral-treated individuals with HIV infection - Defu Yuan; Mingma Li; Ying Zhou; Lingen Shi; Jing Lu; Gengfeng Fu; Bei Wang (Elsevier, 2023)
Antiretroviral therapy (ART) aims to inhibit HIV replication, decrease CD4 T cell loss, and immune function recovery in order to reduce the morbidity and mortality associated with the infection. Treatment should also, improve quality of life and control HIV spread. However, incomplete viral suppression still occurs during ART. Viral suppression and virological failure (VF) thresholds vary between studies in terms of virological rebound (VR) states using different detection thresholds. Further understanding of influencing factors and adverse outcomes in various VR states should provide important guidance for HIV treatment.